PENGARUH KREATIVITAS PRODUK DAN BRAND IMAGE TERHADAP MINAT BELI KAOS NEVADA - Azhari, Ayu; Tjahjono, Endro; Mulyati, Awin (Universitas 17 Agustus 1945 Surabaya, 2020)
Product creativity is a very important step for the survival of the company's productivity. This will have an impact on Brand Image. This study entitled The Effect of Product Creativity and Brand Image on Purchasing Interest in Nevada T-shirts at Matahari Department Store Royal Plaza Surabaya has a problem statement is how much the influence of Product Creativity and Brand image on the purchase interest of Nevada T-shirts at Matahari Department Store Royal Plaza Surabaya. The purpose of this study was to find out and analyze how much influence the creativity of the product and brand image on the purchase interest of Nevada T-shirts at Matahari Department Store Royal Plaza Surabaya. This type of research is a survey or field. The method used is quantitative analysis and data collection techniques with questionnaires. The data used are primary data obtained from subjects namely Nevada booth visitors at Matahari Department Store Royal Plaza Surabaya and secondary data obtained by reading literature, books, articles, journals, data from the internet and thesis or previous research theses. Based on the data analysis, partially and simultaneously the product creativity variable has no significant effect and the brand image has a positive and significant effect on the variable purchase interest of the Nevada T-shirt at Matahari Department Store Royal Plaza Surabaya. In this research, Matahari Department Store is expected to continue to update and always get a good product image in the eyes of the public so that the products produced can meet consumer expectations and increase sales.Keywords: Product Creativity, Brand Image, Purchase Interest